Features of empathy of students of pedagogical specialties - Galina Bezverkhnya; Tsybul'skaVictoria (Kharkiv State Academy of Physical Culture, 2014)
Purpose: to define levels of empathy at students. Material and methods: levels of the manifestation of empathy are studied at students of faculty of the primary education of full-time education and correspondence course (120 persons). The technique of the definition of empathy of I. M. Yusupov was used. Results: the reliable decrease is revealed in the level of empathy to children from the II to the IV course of the full-time education. On the correspondence course the level of empathy to children remains stable on the II and the IV courses. Conclusions: this technique of the definition of the level of empathy allows to judge the professional suitability of those who chooses a pedagogical profession, and helps to define, what profession shouldn't be chosen by graduates of schools because of the incompatibility with the object of the future professional activity.